Can't Buy Me Rights! The Contractual Structure of Asymmetrical Inter-firm Collaborations - Carolin Häussler (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2006)
The efficient allocation of control rights in inter-firm collaborations is a widely emphasized issue. In this paper, I empirically identify control rights and the allocation of these rights using a unique survey data set on collaborations between biotechnology and pharmaceutical firms. Fifteen control rights are identified to make up the structure of deals with five rights being the items of contention in deal making (ownership of patents, production, further development of the technology, the right to manage the collaboration, and the right to market universally). I find that the assignment of control rights is related to the bargaining position of firms and incentive issues. Hence, goliaths -pharmaceutical incumbents- subrogate critical rights to the new ventures when the final outcome of the project is depending on the venture's effort.
urn:nbn:de:bvb:19-epub-13362-0
Keywords: D23; L24; G30; M13; O32; 330; contracts; performance; inter-firm collaboration; biotechnology